Parkinson’s Disease in a Patient with 22q11.2 Deletion Syndrome: The Relevance of Detecting Mosaicisms by Means of Cell-By-Cell Evaluation Techniques - Perandones, Claudia (2015)
We report the case of a male patient from an Ashkenazi Jewish ethnic group with a history of midline defects (congenital heart disease, high-arched palate and bifid uvula). At the age of 46 years, he came to our center complaining of resting tremor, and a neurological examination concluded Parkinson?s disease. As a part of his approach, genetic evaluation was performed. Fluorescence in-situ hybridization (FISH) confirmed a mosaicism of a 22q deletion in 24% of the analyzed blood cells. Also, immunohistochemical studies were performed on samples from the minor salivary glands using a SNCA antibody. Intense SNCA immunoreactive profiles were obtained for cells from the salivary glands of the patient. This is, to our knowledge, the first description of the association of amosaicism of a 22q11.2 microdeletion syndrome with Parkinson?s disease. Our findings suggest that, before excluding the involvement of the 22q11.2 deletion in the etiology of early-onset PD cases, the spectrum of evaluations should be extended to include more sensitive FISH analysis and immunohistochemical studies. The pathogenesis of early-onset PD in patients with 22q11.2 deletion syndrome remains unknown but, if elucidated, it may contribute to understanding the etiology of PD and ultimately to preventionand treatment strategies.